Comparison of four CAD-CAM guides for preparing guiding planes of removable partial dentures. (July 2022) - Bai, Hefei; Ye, Hongqiang; Chen, Hu; Wang, Yong; Zhou, Yongsheng; Sun, Yuchun
Abstract: Background and objective: To evaluate the effect of guiding structure and 3D-printing material of CAD-CAM guides on the accuracy of guiding planes preparation. Methods: Four types of computer-aided design and computer-aided manufacturing (CAD-CAM) guides for preparing guiding planes of removable partial denture (RPD) were designed in two types of guiding structures (triple-constraint and single-plane constraint) and were 3D printed using resin and cobalt-chromium (Co–Cr) alloy. Guiding plane preparation of identical resin casts was performed using CAD-CAM guides (resin template, metal template, resin guided device, and metal guide device) in four test groups and by freehand in the control group (n = 22 per group). All prepared casts were then scanned (Test) and aligned to the reference cast with designed guiding planes. 3D compare analysis was performed and root-mean-square (RMS) values were calculated for assessing the 3D trueness and 3D precision of guiding plane preparation. The angle between the prepared guiding plane (Test) and the designed path of placement of RPD (Reference) was measured for evaluating the direction trueness. Results: RMS values of the metal template group for 3D trueness (39.7 ± 14.6 μm) and 3D precision (28.6 ± 6.8 μm) were significantly lower than that of other groups ( p  < .05). For direction trueness, the metal template group showed the least angle deviation (1.09 ± 0.56°), and the freehand group demonstrated the largest angle deviation (7.03 ± 2.83°). Conclusions: The Co–Cr alloy guides with triple-constraint guiding structure can assist to prepare accurate guiding planes of RPD. Highlights: The CAD-CAM guides assisted procedure can improve tooth preparation of guiding planes, respect to freehand procedure. The rigid triple-constains template can assist to accurately prepare guiding planes without need of direct vision.